Comparative prospective randomized open label trial of synbiotic (bifilac) as an add on therapy with standard treatment in patients with aphthous ulcer - G., Sasikala; Sivaraman, Malar; Dutta, Trayambak; K. R., Dhanasekar (International Journal of Basic & Clinical Pharmacology, 2018)
Background: To trial the safety, efficacy and rapidity of response to a lozenges containing synbiotic in patients with minor aphthous ulcer. Methods: A total of 60 patients were enrolled for the trial after obtaining IEC approval and randomly allocated into two groups. Control “Group A” was administered with conventional treatment i.e., zytee and B complex for 2 weeks and trial “Group B” was administered with Bifilac along with conventional treatment for 2 weeks. The results of this trial were analyzed both subjectively and objectively. Results: Comparing with control group, where standard treatment was used with analgesics and B-complex, the trial group showed a quick relief of pain and helped in reducing mean size of ulcer. Conclusions: This trial was done with synbiotic lozenges in minor aphthous ulcers and it proved to be better alternative for them. Moreover, synbiotics have no adverse effects.